2020
DOI: 10.35741/issn.0258-2724.55.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Twitter Sentiment Analysis Using an Ensemble Majority Vote Classifier

Abstract: Twitter social media data generally uses ambiguous text that can cause difficulty in identifying positive or negative sentiments. There are more than one billion social media messages that need to be stored in a proper database and processed correctly to analyze them. In this paper, an ensemble majority vote classifier to enhance sentiment classification performance and accuracy is proposed. The proposed classification model is combined with four classifiers, using varying techniques—naive Bayes, decision tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…They found that due to factors such as the brevity of tweets, Twitter-specific language [ 30 ], and a class imbalance [ 31 ], classification algorithms achieved an accuracy of around 70%. However, Adwan et al [ 32 ] also reviewed a large number of techniques and they found a mix of accuracy scores, with some papers passing 80% accuracy while others still perform below 80% even with new algorithms [ 33 ]. Among those who have improved their accuracy, some only focus on specific politics-related data sets [ 34 ], some propose methods that require a large number of steps [ 35 ], while others address the issues with tweets, such as Twitter-specific language [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that due to factors such as the brevity of tweets, Twitter-specific language [ 30 ], and a class imbalance [ 31 ], classification algorithms achieved an accuracy of around 70%. However, Adwan et al [ 32 ] also reviewed a large number of techniques and they found a mix of accuracy scores, with some papers passing 80% accuracy while others still perform below 80% even with new algorithms [ 33 ]. Among those who have improved their accuracy, some only focus on specific politics-related data sets [ 34 ], some propose methods that require a large number of steps [ 35 ], while others address the issues with tweets, such as Twitter-specific language [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most models did not consider the diverse features of users. For example, Abbas et al 23 used four classifiers of Naive Bayes, Decision Tree, Multi-Layer Perception and Logistic Regression to integrate a majority voting classifier to identify the negative or positive sentiment of tweets. Vashishtha and Susan 24 used one new unsupervised system based on nine fuzzy rules to calculate and classify the sentiment of social media posts.…”
Section: Related Workmentioning
confidence: 99%
“…In our model, NLP will interpret the text from the OCR phase to give a better understanding of whether the image is Spam or Ham. After pre-processing the extracted text from the OCR phase to get a clean text dataset, NLP uses the bag-of-words [20] method to generate a feature vector to use in the next phase; training the model.…”
Section: Natural Language Processing (Nlp)mentioning
confidence: 99%